Magill's survey of world literature [electronic resource] - Kellman, Steven G. , 1947-; Magill, Frank N. [ (Frank Northen)] , 1907-1997 (Salem Press, 2009)
Offers profiles of major writers outside the United States from all time periods, accompanied by analysis of their significant titles of fiction, drama, poetry, and nonfiction.